Production and molecular identification of polyploids from Bendizao tangerine in Huangyan - ZHANG Chenglei; XIA Zewen; XU Xinyan; LIU Gaoping; PAN Liqin; WU Xiaomeng; GUO Wenwu; XIE Kaidong (Guoshu xuebao, 2025)
[Objective] Bendizao tangerine (Citrus succosa Hort. ex Tanaka), originally from Huangyan, Zhejiang Province, is a representative variety of the regional brand Huangyan Miju. It is an excellent variety for both fresh consumption and processing for canned fruit. In the 1980s, the Bendizao tangerine experienced its peak development period in Huangyan. However, due to long-term asexual propagation, problems such as the decline in yield and quality have emerged in recent years. And due to the seedy nature of Bendizao tangerine and the introduction of numerous of seedless varieties from abroad over the past few decades, the production and planting area of the Bendizao tangerine in Huangyan have declined sharply. Therefore, conducting genetic improvement to produce new seedless germplasms with application potential is an effective strategy to solve the above industrial problems of the Bendizao tangerine and enhance the brand value of Huangyan Miju. The creation of triploids through diploid and tetraploid interploidy cross seems to be an effective way to breed new seedless varieties. When allotetraploids are used as parents in crosses with diploids, the resulting triploid hybrids are expected to inherit excellent traits from all three parental genomes, except for seedlessness. This would facilitates the selection of new varieties that combine seedless fruits with other desirable traits. Based on this strategy, Huazhong Agricultural University previously generated over 3500 triploid plants from more than 80 interploidy crosses, utilizing allotetraploid somatic hybrids as male parents and some local diploid seedy varieties as female parents. However, the creation of allotetraploids using cell fusion is relatively difficult. In contrast, exploring autotetraploids from seedlings based on their morphology is relatively straightforward due to the characteristic of nucellar cells in polyembryonic cultivars being prone to natural doubling. Moreover, utilizing autotetraploids as parents to cross with its corresponding diploids in interploidy crosses can generate autotriploids. This approach is expected to produce seedless fruit without altering other traits of the original variety, thereby enhancing its application value. Therefore, in this study, cell engineering techniques including interploidy hybridization and exploring polyploids from seedlings based on their morphology were utilized to produce or explore new polyploid germplasms from Bendizao tangerine for breeding elite resources for the healthy development of Huangyan tangerine. [Methods] For tetraploid exploration, the seeds of Bendizao tangerine were sown in the pots after peeling off the seed coats and being accelerated germination in a thermostat, then cultivated in a plant growth chamber. After the seedlings grew with three or more leaves, putative polyploids were screened according to the morphological feature of polyploid plants and their ploidy level were further confirmed by flow cytometric analysis. For triploid production, interploidy hybridization and embryo rescue were employed. In this study, an interploidy cross was conducted with Bendizao tangerine as female parent and a sexual allotetraploid hybrid (abbreviated as BDZNS) from the cross between Bendizao tangerine and NS as male parent. The young fruits were collected 90 days after pollination. After extracted from the young fruits, the immature seeds were in vitro cultured in medium germination. When the seedling regenerated, their ploidy level was determined by the flow cytometry and their genetic origin were determined using SSR markers. [Results] For tetraploid exploration, more than 1500 mature fruits of Bendizao tangerine were collected, and more than 7500 seeds were obtained. The seeds were sowed in the pots and cultivated in a plant growth chamber for approximately one month, and over 9000 seedlings were obtained. Based on the morphology trait screening, 51 suspected polyploids were screened from the seedlings. 23 tetraploids and one triploid were totally obtained through analyzing the ploidy level using flow cytometry. For triploid production, an interploidy cross was conducted with Bendizao tangerine as the female parent and allotetraploid BDZNS as the male parent. Totally 155 flowers were pollinated, and 35 fruits were set. On the 90th days after pollination, all young fruits were picked and 105 young ovules were extracted and subjected to in vitro rescue culture. After shooting and rooting induction, 78 regenerated plants were obtained, among them eight plants were proved triploids by flow cytometry analysis. The genetic origin of all the polyploids obtained was carried out with SSR molecular markers. Among the polyploids identified from the seedlings, 19 tetraploids exhibited an identical band pattern to that of Bendizao tangerine, suggesting that they might originate from the natural doubling of nucellar cells in Bendizao tangerine. The remaining four tetraploids and one triploid exhibited an additional band that was not present in Bendizao tangerine, indicating that they were likely sexual hybrids of Bendizao tangerine with other citrus varieties. The eight triploids produced by interploidy hybridization contained both female-specific and male-specific bands, indicating that they were sexual offspring resulting from contributions of both parents. [Conclusion] The novel polyploid germplasms developed in this study would provide a valuable material foundation for the seedless breeding of Bendizao tangerine and for enhancing the fruit quality of Huangyan Miju.